2020
DOI: 10.1002/pst.1992
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment designs using placebo nonresponders

Abstract: Enrichment designs that select placebo nonresponders have gained much attention during the last years in areas with high placebo response rates, eg, in depression. Proposals were made that re-randomize patients who did not respond to placebo during a first study phase as the sequential parallel design (SPD). This design uses in a second phase an enriched patient population where the treatment effect is expected to be more pronounced. This may be problematic if an effect in the overall population is claimed. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It can be resolved if the correlation is the same for both the placebo–drug and placebo–placebo groups. However, as pointed out by Benda and Haenisch 21 in the context of the sequential parallel comparison design, in turn, enriching for placebo nonresponders is inefficient for a trial power. As shown in our numerical investigation results, it also holds good for the PLD.…”
Section: Discussionmentioning
confidence: 99%
“…It can be resolved if the correlation is the same for both the placebo–drug and placebo–placebo groups. However, as pointed out by Benda and Haenisch 21 in the context of the sequential parallel comparison design, in turn, enriching for placebo nonresponders is inefficient for a trial power. As shown in our numerical investigation results, it also holds good for the PLD.…”
Section: Discussionmentioning
confidence: 99%
“…Cui, Ogbagaber, and Hung (2019) improved the OLS estimator by considering multiple correlation structures between Stages 1 and 2. Similar to the suggestion by Chen et al (2011), Benda and Haenisch (2020) suggested a bias in the OLS estimator and proposed a new estimator constructed by introducing an interaction between the treatment effects of Stages 1 and 2. Rybin et al (2018) proposed a novel treatment effect estimation method that uses an expectation-maximization (EM) algorithm wherein the outcomes corresponding to placebo responders are regarded as missing variables.…”
Section: Introductionmentioning
confidence: 91%
“…In the SPCD framework, it is often assumed that δ 1 = δ 2 because the estimand attributes of δ 1 and δ 2 can be assumed as equivalent. However, Doros et al (2013), Chi et al (2016), and Benda and Haenisch (2020) suggested that δ 2 generally differs from δ 3 . Therefore, the hypothesis of the statistical test should be carefully defined considering the definition of the treatment effects.…”
Section: Definition Of Treatment Effects and Their Estimatormentioning
confidence: 99%